Personalized Cancer Therapy: Advancement in Biomarker-Based Treatment Strategies for Non-Small Cell Lung Cancer - Rehman, Ubaid Ur; Quratulain Badar; Abdoon, Yasser Hijazi; Muhammad Ghous; Tahir Aslam; Aslam, Minahal; Ali, Syed Rizvan (Indus Journal of Bioscience Research, 2025)
This study sought to assess the effectiveness of biomarker-directed personalized therapies for the treatment of non-small cell lung cancer (NSCLC) targeting actionable genetic mutations like EGFR, ALK, and PD-L1. A prospective observational study was performed on 200 NSCLC patients with established genetic alterations, divided into four groups: EGFR-mutant, ALK-rearranged, PD-L1-positive, and wild-type (no biomarkers). Patients were treated with targeted therapies (e.g., EGFR inhibitors, ALK inhibitors, PD-1 inhibitors) or platinum-based chemotherapy. EGFR-mutant patients had the best response rates (70%) and overall survival (OS) of 24 months. ALK-rearranged and PD-L1-positive patients also had good outcomes, with response rates of 65% and 60%, respectively, and OS of 22 and 20 months. In contrast, the wild-type group had the worst response rate (45%) and OS (16 months). The study also found significantly fewer adverse events in the EGFR and ALK treatment groups than with chemotherapy. Kaplan-Meier analysis indicated better progression-free survival (PFS) in the biomarker-targeted groups. Statistical analysis using ANOVA and chi-square tests proved significant differences in response rates (p-value < 0.05), validating the effectiveness of biomarker-directed personalized treatment approaches. These findings suggest that biomarker-directed therapies can significantly enhance patient outcomes compared to standard chemotherapy, highlighting the value of biomarker testing in clinical practice.